Holding open spaces to explore beyond: Toward a different conceptualization of specialization in high-performance sport - Richard, V.; Cairney, J.; Woods, C. T. (Frontiers in Psychology, 2023)
This conceptual analysis aims to challenge the state of high-performance sport by questioning the concept of specialization. To start, we offer a brief, but critical overview of what specialization currently entails. Then, shifting the paradigm, we suggest an expansion rather than a reduction of developmental possibilities once an athlete reaches the "top". Specifically, rather than athletes conforming to national standards imposed by governing bodies about what it means to be "elite", we suggest sport systems consider a person-environment fit approach to support ongoing development. Drawing on an ecological dynamics rationale and various socio-cultural theories, we explore how concepts such as affordances and perspectives can be harnessed to create a better "fit" between athletes` action capabilities and the opportunities within their broader environment. Our conception of specialization requires moving away from a definition of success based on the accumulation of medals, toward one that accounts for the exploration and achievement of the possible. We argue that a person-environment fit welcomes diversity, so long as it sustains the person`s health, wellbeing, and performance. This, it is suggested, is about collectively holding open spaces for each other to explore beyond the constraints of high-performance sport, encouraging all to carry on their lives in directions meaningfully impactful for them. We conclude this conceptual analysis with a brief case example demonstrating what our theorizing could look like in practice.